2021
DOI: 10.14338/ijpt-20-00066.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following Dose-Escalated Proton Therapy for Skull-Base Chordoma

Abstract: Purpose To evaluate the effectiveness of external-beam proton therapy (PT) on local control and survival in patients with skull-base chordoma. Materials and Methods We reviewed the medical records of patients with skull-base chordoma treated with definitive or adjuvant high-dose PT and updated their follow-up when feasible. We assessed overall survival, disease-specific survival, local control, and freedom from distant metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…This multicenter study underscores the efficacy of proton therapy as a potent adjuvant to resection when dealing with chordomas, presenting compelling evidence of its superiority over traditional photon radiotherapy in curbing recurrence. 15 Notably, logistic regression analysis accentuated a significant reduction in the risk associated with recurrence in cases managed with proton therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This multicenter study underscores the efficacy of proton therapy as a potent adjuvant to resection when dealing with chordomas, presenting compelling evidence of its superiority over traditional photon radiotherapy in curbing recurrence. 15 Notably, logistic regression analysis accentuated a significant reduction in the risk associated with recurrence in cases managed with proton therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are in accordance with earlier studies suggesting the efficacy of proton therapy in managing chordomas. 15,[17][18][19] Yet, what distinguishes our study from these earlier ones is the incorporation of tree-based machine learning models, shedding light on crucial predictive variables.…”
Section: Discussionmentioning
confidence: 99%
“…For three-fraction SRS for brain metastases, normal brain tissue V18 < 30 cc and V23 < 7 cc were associated with <10% risk of brain necrosis. Finally, we evaluate the results of this study based on the latest reports [14,[21][22][23]31,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. According to the latest reports, the 5-year local recurrence rate for chordoma was about 15 to 35%, while for chondrosarcoma, it was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46] Other significant series are summarised in Table 1. 15,37,[47][48][49] To date, there have been no randomised studies comparing proton therapy and photon therapy. In a meta-analysis spanning the years 1999 to 2010, Di Maio et al 50 concluded that there was no significant difference in 5-year overall survival based on the adjuvant radiation modality, whether it be proton therapy, carbon ion therapy, Gamma knife radiosurgery, or fractionated photon radiation.…”
Section: Review Of Evidence Regarding Use Of Radiotherapymentioning
confidence: 99%
“…Several excellent reviews of the literature for proton therapy in skull base chordomas have been published recently including systematic reviews 42–46 . Other significant series are summarised in Table 1 15,37,47–49 …”
Section: Introductionmentioning
confidence: 99%